Preparation, Antioxidant Properties and Ability to Increase Intracellular NO of a New Pyridoxine Derivative B6NO - Anastasia Balakina; Tatyana Prikhodchenko; Vera Amozova; Tatyana Stupina; Victoria Mumyatova; Margarita Neganova; Ilya Yakushev; Alexey Kornev; Svyatoslav Gadomsky; Boris Fedorov; Denis Mishchenko (MDPI AG, 2021)
In the case of various pathologies, an imbalance between ROS generation and the endogenous AOS can be observed, which leads to excessive ROS accumulation, intensification of LPO processes, and oxidative stress. For the prevention of diseases associated with oxidative stress, drugs with antioxidant activity can be used. The cytotoxic, antioxidant, and NO-donor properties of the new hybrid compound B6NO (di(3-hydroxy-4,5-bis(hydroxymethyl)-2-methylpyridinium) salt of 2-(nitrooxy)butanedioic acid) were studied. It was determined that B6NO chelates iron ions by 94%, which indicates B6NO's ability to block the Fenton reaction. The hybrid compound B6NO inhibits the process of initiated lipid peroxidation more effectively than pyridoxine. It was shown that B6NO exhibits antioxidant properties by decreasing ROS concentration in normal cells during the oxidative stress induction by tert-Butyl peroxide. At the same time, the B6NO antioxidant activity on tumor cells was significantly lower. B6NO significantly increases the intracellular nitrogen monoxide accumulation and showed low cytotoxicity for normal cells (IC50 > 4 mM). Thus, the results indicate a high potential of the B6NO as an antioxidant compound.